Generations & geographies in the visual arts: feminist readings - Pollock, Griselda.. (Routledge, 1996)
In Generations and Geographies, the challenge of contemporary feminist theory encounters the provocation of the visual arts made by women in the twentieth century. The major issue is difference: sexual, cultural and social. Generations points to the singularity of each artist's creative negotiation of time and historical and political circumstance; Geographies calls attention to the significance of place, location and cultural diversity, connecting issues of sexuality to those of nationality, imperialism, migration, diaspora and genocide.Generations and Geographies is framed by theoretical debates in cultural analysis by Griselda Pollock, Mieke Bal, Elisabeth Bronfen and Irit Rogoff, and two historical analyses of representations of the female nude by Rosemary Betterton and Nanette Salomon. Essays on international contemporary art discuss artistic practice by women working in both western and non-western contexts, focusing on themes of the mother, the body, the land and history/memory. The artists discussed include the French performance artist Orlan, the Cuban American artist Ana Mendieta and Jenny Saville from Britain, the Chilean artist Cecilia Vicuna, Shimada Yoshiko from Japan, the Korean artist Re-Hyun Park and the Korean/Canadian artist Jin-me Yoon, Bracha Lichtenberg Ettinger from Israel and the American artist Cindy Sherman. British/Zanzibari artist Lubaina Himid provides specially commissioned artists' pages on the theme of history, location and displacement.
Keywords: 1900-1999; approches et analyses; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; intersectionnalité; maternité; point de vue situé; premier cycle; périodes historiques; ressource en ligne; thématiques

De la mère patriarcale à la mère légendaire : Triptyque lesbien de Jovette Marchessault - Saint-Martin, Lori (Voix et Images, 1991)
Keywords: amériques; approches et analyses; arts; discipline; histoire et politique; maternité; patriarcat; personnes lesbiennes; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; études littéraires

Journal de la création - Huston, Nancy (Seuil, 1990)
Pendant des millénaires, tout paraissait simple : aux hommes la création, aux femmes la procréation ; aux hommes l'esprit et aux femmes le corps. L'émancipation féminine a bousculé cette distribution des rôles et mis à mal des métaphores séculaires : la muse féminine, l'œuvre d'art comme amante ou comme " enfant " de l'artiste. Mais trouver un nouveau modus vivendi n'est pas facile pour autant. Mettant à profit une certaine et curieuse forme de clairvoyance liée, dans son esprit, aux métamorphoses de son corps de femme enceinte, Nancy Huston s'est penchée sur les histoires souvent douloureuses de Sand et Musset, Virginia et Leonard Woolf, Scott et Zelda Fitzgerald, Sartre et Beauvoir. Le récit de ses recherches sur les couples d'écrivains et le journal de sa propre grossesse se croisent, se répondent et se complètent pour évoquer les mystères de l'amour, de l'inspiration, du couple et de la création.
Donné en lecture: p.11-56
Keywords: 1900-1999; 1980-1989; amériques; corps; cours; discipline; europe; fem1000; lit2815; lit3220; lit3495; littérature; maternité; premier cycle; périodes historiques; régions géographiques; thématiques; études culturelles; études littéraires

The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Number: 3
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques

Écrire un théâtre musical : transit - Jonassaint, Jean (Dérives, 1984)
Entretien avec Micheline Coulombe Saint-Marcoux et France Théoret
Keywords: 1900-1999; 1980-1989; amériques; arts; discipline; maternité; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; théâtre; travail; écriture des femmes*

Le torrent - Hébert, Anne (Beauchemin, 1950)
Un enfant prisonnier de sa mère, au cœur d’un domaine bruissant d’eaux sauvages (Le torrent) ; un instant de tendresse dérisoire, qui change à jamais la vie sage d’une ouvrière-tricoteuse (La robe corail) ; l’exode vécu comme une fête par une petite serveuse, enfin libre au milieu des dangers (Le printemps de Catherine) ; la visite quotidienne d’un homme frustré à sa sœur, qu’il espère chaque jour trouver morte (La maison de l’esplanade)... Si divers que soient les paysages, les milieux, les situations, ces nouvelles d’Anne Hébert sont toutes tendues par une même force : celle de la passion (amour ou haine) qui saisit l’être dans les premiers temps de son existence, qui ne pourra être "dite" parce que la famille, la société ou la solitude refusent cette parole, et qui ne se délivrera d’elle-même que dans la mort — meurtre ou suicide. On retrouvera, à la mesure de ces thèmes, les qualités que "Les chambres de bois" et les "Poèmes" avaient révélées : sens concret de l’instant, vigueur et brièveté de l’écriture, saveur terrienne des images et des mots.
Section: 171 pages
Keywords: 1900-1999; 1990-1999; amériques; arts; canada; cours; discipline; histoire et politique; lit3495; littérature; maternité; premier cycle; périodes historiques; québec; régions géographiques; thématiques; études littéraires